Spectroscopic (FTIR, 1H NMR) and SEM investigation of physicochemical structure changes of coal subjected to microwave-assisted oxidant stimulation. (1st June 2022) - Li, He; Xu, Chaoping; Ni, Guanhua; Lu, Jiexin; Lu, Yi; Shi, Shiliang; Li, Min; Ye, Qing
Highlights: Microwave-assisted oxidation causes oligomerization and polymerization of coal. Condensation polymerization improves the maturation and aromaticity of coal. The coal surface becomes porous with crisscrossed fractures after stimulation. The NMR permeability of coal increases 471–1425% after stimulation. Abstract: Owing to the sub-economic permeability, coalbed methane (CBM) reservoir usually requires stimulation. Novel CBM stimulation approaches have been proposed such as CO2 injection, liquid nitrogen frozen, microwave irradiation, high-voltage electrical pulse, and acid/oxidant treatment, but none is ubiquitously successful. Oxidant treatment targets the removal of organic micromolecules or minerals in coal, thereby etching pores and fractures. However, the oxidants exhibit low activity and permeation at ambient temperature. Oxidant corrosion also generates coal fines which can accumulate and jam in the fractures. Microwave heating may be a promising approach to overcome these limitations. This paper introduces the concept of using microwave-assisted oxidation for permeability enhancement. Fourier transform infrared spectroscopy (FTIR), 1 H low-field nuclear magnetic resonance ( 1 H NMR), and Scanning electron microscope (SEM) were used to assess the physicochemical structure changes of coal prior to and after stimulation. Results show that Microwave-assisted Fenton's reagent and Na2 S2 O8 oxidation can break the self-associating hydrogen bonds in carboxyl, alcohol, and phenol, converting them into ether groups. The removal of oxygen-containing functional groups results in oligomerization and polymerization. Microwave-assisted condensation polymerization improves the maturation and aromaticity of coal. Microwave not only causes pore opening and expansion but also leads to pore collapse and closure. Oxidation not only induces dissolution, swelling, and breakage of coal but also soften the coal matrix, leading to a drop in the producible porosity. After microwave-assisted oxidation, the coal surface becomes porous with crisscrossed fractures. Combined with microwave fracturing, the oxidant is not reacting at the coal surface, but rather it is penetrating into the coal matrix and reacting internally. As a result, the NMR permeability of coal increases 471–1425%. This study reveals the potential of microwave-assisted oxidation to enhance coal permeability.